PESQUISA EM DESIGN EDUCACIONAL: CONTRIBUIÇÕES PARA O DESENVOLVIMENTO PROFISSIONAL DE PESQUISADORES - Tamiosso, Raquel Tusi (2024)
This research emerged from the needs and wishes felt by initial educational design researchers from a study group named Studies and Research in Educational Design Research Group (in Portuguese, Grupo de Estudos e Pesquisa em Design Educacional – GEPDE), linked to the Postgraduate Program in Science and Mathematics Teaching at the Franciscan University, Santa Maria-Brazil. The aforementioned group started its activities in 2018, with a view to deepening its knowledge regarding educational design research (EDR). During the group's journey, some questions about conducting EDR in a quality and meaningful way have emerged, culminating in the search for theoretical and practical aspects that could help beginner researchers to carry out this type of research. Based on the literature, it is possible to consider EDR as a complex research genre to be conducted due to its several characteristics, such as: a) it involves real contexts of teaching and learning, which contemplates several variables; b) it advocates collaboration between education professionals; c) it establishes the connection between theory and practice; d) it predicts iterative cycles of refinement; e) it is responsive and, therefore, needs to be flexible and dynamic, according to the events of reality. Therefore, it is essential to think about the characteristics of an intervention to promote the professional development of initial educational design researchers who wish to use EDR in their projects. Thus, the general goal of this research is to investigate the theoretical and practical aspects to support the professional development of an initial educational design research community that aims to improve the teaching and learning of Science and Mathematics in Brazil along with EDR. To achieve this goal, some specific objectives were established: I) To identify existent research and resources regarding EDR that can contribute to this research; II) To identify the needs and wishes that are felt by the initial educational design researchers, as well as the knowledge, skills, and attitudes that they have regarding EDR; III) To establish design requirements and design propositions in order to guide the elaboration of the design plan; IV) To develop and evaluate a prototype, based on the design plan, in order to support the professional development of an initial educational design research community; and V) To investigate to what extent the built design and implemented intervention are effective in supporting and increasing new design researchers’ knowledge, skills, and attitudes. The EDR was adopted as the research approach of the research development, according to the model established by McKenney and Reeves (2019). This approach is quali-quantitative, allowing the use of different strategies and instruments for data collection and analysis. The model established by McKenney and Reeves (2019) advocates the realization of three main phases: analysis and exploration; design and construction; evaluation and reflection. Five studies were established, aligned with the specific objectives, and related to the three main phases of EDR. In the analysis and exploration phase, it is necessary to understand the problem that is being investigated well. To accomplish this phase, studies 1 and 2 were carried out. Study 1 is related to the specific objective I, and was accomplished through the following actions: literature review regarding EDR; mapping of Brazilians’ masters and doctoral theses that adopted EDR; searching for knowledge abroad: an experience with Prof. Susan McKenney (EDR expert); construction of a theoretical framework with relevant knowledge, skills, and attitudes to an educational design researcher to have. The specific objective II recommends field investigations to understand the needs and wishes felt by the research participants and was conducted through Study 2. The actions developed to achieve study 2 were the following: interviews with researchers’ members of the GEPDE group; elaboration and application of a survey, based on the theoretical framework, especially for the GEPDE’s researchers, but also other researchers interested in participating; establishment of networking with other EDR groups in Brazil and around the world. The subsequent phase, called design and construction, refers to the development of a plan for a potential design that contributes to the problem that is being investigated, as well as the construction of solution prototypes. Thus, the fulfillment of Studies 1 and 2 and their respective actions enabled Study 3, related to the specific objective III, which consists of the systematization of the most relevant aspects arising from the phase of analysis and exploration to support the design planning. After the design planning, there is the construction of a prototype, which was intended by Study 4, aiming at the fulfillment of specific objective IV, through the construction of the first solution prototype. The obtained results enabled addressing the proposed research question, as the studies and actions undertaken directed the researchers towards the most suitable theoretical and practical elements to provide support, assistance, and professional development to initial educational design researchers. The design idea consists of a virtual environment, considering that the members of GEPDE have limited time available for synchronous meetings due to their professional activities. Additionally, the results from the analysis and exploration phase indicated the importance of networking – communication and exchange of experiences among educational design researchers. Consequently, this environment was thought as a space specifically intended for educational design researchers, whether affiliated with GEPDE or not. Furthermore, all the content within the virtual environment, as well as its associated social media, is being prepared to be bilingual (Portuguese and English), precisely to foster communication between educational design researchers in Brazil and around the world.